Témoignages de la Guerre des Gaules dans le bassin clermontois, nouveaux apports - Yann Deberge; François Baucheron; Ulysse Cabezuelo; Pierre Caillat; Esther Gatto; Christophe Landry; Daniel Leguet; Jean-François Pasty; Thomas Pertlweiser; Christine Vermeulen; Gérard Vernet (Revue Archéologique du Centre de la France)
The location of the ancient Gergovia and the Caesarian siege works has been known for several years, at least within the scientific community. An expert mission conducted in the mid-1990s has enabled the validation of the layout of some of the fortifications as were described in research at the end of the Second Empire.The proliferation of archaeological work in this area of the Clermont bassin has enabled us to specify the route of Caesar’s military configuration set up in front of Gergovia in 52 BC.The discovery of new property remains (ditches, human burials and horse burials, sections of track) and home furnishings (late-Republican militaria) makes it possible to better understand the influence of the battlefield and lead to the formulation of new hypotheses about the course of the siege of the oppidum.